2022
DOI: 10.1021/acs.jpcc.1c09537
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laser Excitation Wavelength and Power in the Fano Resonance Scattering in RFe0.50Cr0.50O3 (R = Sm, Er, and Eu): A Brief Raman Study

Abstract: Here in the present report, we have extensively studied the impact of the excitation laser wavelength and laser power on the Raman spectrum of mixed Fe-Cr-based rare-earth perovskites. Resonant and excitation laser power experiments carried out for these samples suggest the orbital-mediated lattice rearrangement because of electronic excitation from Cr3+(d3 )-O2–-Fe3+(d5 ) ions, which results in an antiresonance dip around 600 cm–1. The presence of an antiresonance dip even at low laser power is ascribed to Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Researchers have employed the Fano resonance model to describe the signature of electron-phonon coupling (EPC) by analyzing the lineshape of Raman modes. In addition, there have been reports that indicate the excitation laser power-induced EPC effects in some materials provoked by elevated temperature (∼thermal disorder) via the light–matter interactions, which emphasize the sensitivity of such phenomena. Also, since the signature of disorder in a system could be probed through the Raman mode width , as the disorder may alter the phonon lifetime within the system, a recent study had demonstrated the covariation of EPC strength in semiconductors with disorder via application of RS and optical absorption spectroscopy (OAS), that is, a symmetrically broadened peak due to disorder may tend to acquire asymmetric profile in case when disorder may provide sufficient scattering regions for significant electron–phonon interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have employed the Fano resonance model to describe the signature of electron-phonon coupling (EPC) by analyzing the lineshape of Raman modes. In addition, there have been reports that indicate the excitation laser power-induced EPC effects in some materials provoked by elevated temperature (∼thermal disorder) via the light–matter interactions, which emphasize the sensitivity of such phenomena. Also, since the signature of disorder in a system could be probed through the Raman mode width , as the disorder may alter the phonon lifetime within the system, a recent study had demonstrated the covariation of EPC strength in semiconductors with disorder via application of RS and optical absorption spectroscopy (OAS), that is, a symmetrically broadened peak due to disorder may tend to acquire asymmetric profile in case when disorder may provide sufficient scattering regions for significant electron–phonon interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Orthonormality condition applies on α and β 47 . Considering the ground state i, Raman tensor components will uphold the wavenumber‐dispersed asymmetry within the ϒ space.…”
Section: Resultsmentioning
confidence: 99%
“…treatment. 47 The phonon energy E ρ should lie within the span of electronic continuum energy E ϰ ð Þ. Furthermore, j ρi andj ϰi may interact to generate a renormalized (mixed or hybrid) state j Υi given by, 24,25 Υi ¼…”
Section: Introspecting the Effect Of Excitation Strength On Fano Inte...mentioning
confidence: 99%
“…Silver brushed pellets were cofired at 500 °C for an hour to build conducting layers as an electrode on the surface of the pellet. An energy-dispersive spectrometer attached to an air-cooled solid-state laser kit (excitation wavelength = 785 nm) having a charge-coupled-device detector has been used to study Raman spectroscopy measurements at room and high temperatures with a laser power of 4.12 mW on the sample surface and focused with an objective of 50×. At last, room-temperature and high-temperature optical absorption spectroscopy analyses have been performed to investigate the signature of defect states in the energy range 1.5–5 eV in the L15C sample using a Cary-60 UV–vis–NIR spectrophotometer attached with a Harrick Video-Barrelino diffuse reflectance probe. …”
Section: Methodsmentioning
confidence: 99%